Co-teaching at school: a possible way for inclusive education (Research, Society and Development, 2018)
This article intend to do a first explanation of the studies on co-teaching at inclusive classrooms. It is a literature review on positive co-teaching results in some countries around the world and especially in Brazil, where academic research of this subject is still rare. The purpose of this article is to present a part an the existing literature on co-teaching at inclusive classrooms, revisiting authors and structuring some of their ideas, to contribute to the general framework on co-teaching in Brazil. This article is meant to be added with the same direction about co-teaching as an important strategy for inclusion. For the research were selected books, scientific articles and official publications to show some aspects on the subject in some countries in the world and in Brazil. We can first suggest that co-teaching has a positive effected at inclusive classrooms.